Biology : life on earth - Audesirk, Gerald; Auderisk, Teresa (New York : Macmillan Publishing Company, 1989)
Textbooks designed for nonmajors courses in biology should be a breed apart from majors text, because the students are very different.
Unit 1. The life of a cell -- Unit 2. Inheritance -- Unit 3. Evolution -- Unit 4. Anatomy and physiology of plants and animals -- Unit 5. Ecology.
Includes bibliographical references and index.
Keywords: BIOLOGY